Peasant household and land community in Ukrainian SSR (1922–1930s) - Калініченко, В'ячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
Research aim. Analyze the relationships between the peasant household and land community in the Ukrainian SSR in 1922-1930s.Methodology of the research. The methodological basis of the study is the principles of historicism, objectivity, systematic scientific analysis and synthesis. Objectivity in the study is revealed in the identification of potential opportunities for the development of the agricultural sector of the economy. The principle of historicism provides a focus on the land community activities as a process that developed over time in aggregate of historical interconnections and interdependencies. General scientific and specific historical methods that are aligned with the historical analysis are used in the research. Analysis of the historiography has led to the use of analysis, synthesis, generalization, classification. The systematization method was used in the study of archival materials. The analysis, typologization, classification of the reports of the general assembly of land communities, letters and complaints to the authorities allowed to trace the course of the relationships peasant household and land community.The scientific novelty of the research is further substantiation of the holistic concept of the land community organization and activity in the Soviet Ukrainian village. The essence of the concept: the institute of land communities of the Soviet Ukrainian village in the 1922-1930s played a leading role in the economic and social life of the village, in relations with the Soviet authorities. It was a self-governing and self-regulating organization created by the peasants themselves and based on the Ukrainian historical traditions. The land community experience as a vertical type cooperative can be used in today's Ukrainian village to preserve the peasantry as a stratum of Ukrainian society. There were investigated following issues: the peasant household right to land within the land community; membership in peasant household and rights of its members; entrance and exit from the peasant household; the rights and responsibilities of the head; personal property and property of the household; division of the households; distribution of escheated households land and property.It is shown how the land community resolved disputes between peasants over the issues outlined above using official and customary law. Conclusions. The peasant household is an integral part of the land community. Land community, as a union of peasant households, had inseparability and intertwining of functions in its activity.